Influence of heterogeneities on mechanical properties: Virtual material concept. (30th January 2019) - Zhuravlev, R.; Guérard, S.; Froustey, C.
Highlights: VM approach allows the study of theoretical case in connection with the real experiment. Analytical approach to study isotropy of heterogeneous specimens was suggested. The specimens behaviour significantly depends on the volume fraction of inclusions. The specimens behaviour weakly depends on the size of inclusions. VM approach can be used in tasks of homogenization and numerical optimization. Abstract: The present article is connected to the study of a bituminous mixture (BM) material, used on modern railway track as sub-ballast layer. Influence of size and volume fraction of rigid monodisperse spherical inclusions, randomly packed into a hyperelastic matrix, on the mechanical behavior of an obtained composite structure was investigated using "Virtual Material" approach. 3D geometry of inclusions was defined and used for 3D printing and 3D finite element modeling. This approach allows a numerical study of a theoretical case without losing connection with real experiment (by means of direct geometrical correspondence). Parameters of 7 specimens were chosen in accordance with a Doehlert experimental design. Analysis performed on the basis of the "response surfaces" approach has shown that mechanical parameters of studied specimens have a strong dependence on the value of inclusions volume fraction and almost no dependence on the value of the size of inclusions. Stress/strain concentrations were analyzed using FE method in order to find and to visualize load-bearing chains going through the matrix. It was found that Von Mises stress in load-bearing chains is almost 8 times higher than the average in the matrix.